Effect of Sonic Bloom Treatment on the Growth of Green Mustard and Pak Choi - Asritanarni Munar; Mukhtar Yusuf; Reza Azhari; Dafni Mawar Tarigan; Wan Arfiani Barus; Imam Hartono Bangun (Universitas Panji Sakti, 2026)
Productivity of green mustard (Brassica juncea L.) and pak choi (Brassica rapa L.) is often constrained by suboptimal cultivation practices. Sound-based stimulation, such as Sonic Bloom, offers a novel approach to enhance plant growth, yet comparative evidence across sound types remains limited. This study evaluated the effects of Qur’anic recitation and classical music on the growth and yield of both crops. A Randomized Block Design with a non-factorial time-series approach was implemented from July to September 2022. Two plant species (J1: green mustard; J2: pak choi) and three treatments were tested: S0 (control), S1 (Qur’anic recitation), and S2 (classical music). Sound exposure (90 dB, 20–14,500 Hz) was applied daily for 2 hours, beginning 7 days after planting and continuing until harvest (24 DAP). Growth parameters and biomass were analyzed using ANOVA and Tukey’s HSD (5%). Classical music (S2) significantly enhanced early growth, with plant height increases reaching 102.08% in green mustard and 91.16% in pak choi (6–12 DAP). Green mustard consistently outperformed pak choi across stages (77.88% vs 60.92% at 12–18 DAP; 42.07% vs 27.72% at 18–24 DAP). Leaf number increased up to 44.12%, and leaf area reached 208.74% under S2. Qur’anic recitation (S1) showed stronger effects at later stages, including higher dry root weight (0.34 g). Chlorophyll content was higher in green mustard but was not significantly affected by treatments. Classical music promotes early vegetative growth, while Qur’anic recitation supports sustained development. Sound-based stimulation represents a promising, sustainable strategy to enhance leafy vegetable productivity.